2020
DOI: 10.1080/21663831.2020.1724204
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity and electrical transport properties of double-A-layer MAX phase Mo2Ga2C

Abstract: The present study reports the thermal conductivity and electrical transport properties of Mo 2 Ga 2 C, which is the first member of double-A-layer MAX phases. Dense bulk samples of Mo 2 Ga 2 C were prepared by vacuum hot pressing. At room temperature, the thermal conductivity was measured to be 14.8 ± 1.0 W/(m•K) and the electrical resistivity was 0.525 ± 0.052 µ •m. Mo 2 Ga 2 C follows the Wiedemann-Franz law and the Lorenz number is 2.22×10 −8 W K −2 . Mo 2 Ga 2 C is a superconductor with a transition temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…It was found that the RT thermal conductivity of Mo 2 Ga 2 C is 14.8 ± 1.0 W (m K) −1 , the RT resistivity is 0.525 ± 0.052 μΩ m, and the Lorenz number is 2.22 × 10 −8 WΩ K −2 . Importantly, Mo 2 Ga 2 C has superconductivity, and the superconducting transition temperature is 5.1 K [208]. Porrati used Nb(NMe 2 ) 3 (N-t-Bu) as the precursor to prepare two-dimensional nanowires and self-supporting three-dimensional nanowires through focused electron beam-induced deposition (FEBID) and focused ion [204].…”
Section: Superconductormentioning
confidence: 99%
“…It was found that the RT thermal conductivity of Mo 2 Ga 2 C is 14.8 ± 1.0 W (m K) −1 , the RT resistivity is 0.525 ± 0.052 μΩ m, and the Lorenz number is 2.22 × 10 −8 WΩ K −2 . Importantly, Mo 2 Ga 2 C has superconductivity, and the superconducting transition temperature is 5.1 K [208]. Porrati used Nb(NMe 2 ) 3 (N-t-Bu) as the precursor to prepare two-dimensional nanowires and self-supporting three-dimensional nanowires through focused electron beam-induced deposition (FEBID) and focused ion [204].…”
Section: Superconductormentioning
confidence: 99%
“…The fabrication details of Mo2Ga2C were described elsewhere [25,26]. In brief, Mo2C powders (Sigma Aldrich Co., USA, 99.5 wt.%, 325 mesh) and Ga (Beijing Xingrongyuan Co., China, 99.99 wt.%) were mixed with the molar ratio of 1:5, vacuum sealed in a glass tube and annealed at 650 ℃ for 60 h. Thereafter, the samples were immersed in HCl for 48 h to remove extra Ga, followed by centrifugal washing and drying in vacuum.…”
Section: Methodsmentioning
confidence: 99%
“…However, there was little research on Mo2Ga2C in the field of high temperature. He et al [25] found Mo2Ga2C will decompose when the temperature is higher than 700 o C and new study of Jin et al found that Mo2Ga2C's thermal conductivity and electrical resistivity were lower than those of most MAX phases probably due to the extra Ga layer [26].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the huge demand and interest in MXenes during the last years have relaunched the synthesis of new phases, such as containing double A-layer (ie Mo 2 Ga 2 C) and compositions with noble metals as "A" element (ie Ti 2 AuN). 298,299 These MAX phases with novel layer-structure/element might exhibit new properties or applications, such as superconductivity or unusual magnetic response. Another aspect is the development of phase diagrams for systems that are difficult to synthesize such as Zr-Al-C.…”
Section: Max Phases and Solid Solutionsmentioning
confidence: 99%
“…However, investigating new solid solutions and/or doping with catalyst elements such as Pd, Pt, Ni, Mo, Ru, etc would be of interest. In fact, the huge demand and interest in MXenes during the last years have relaunched the synthesis of new phases, such as containing double A‐layer (ie Mo 2 Ga 2 C) and compositions with noble metals as “A” element (ie Ti 2 AuN) 298,299 . These MAX phases with novel layer‐structure/element might exhibit new properties or applications, such as superconductivity or unusual magnetic response.…”
Section: Future Challengesmentioning
confidence: 99%